Hubungan Pengetahuan Ibu Tentang Gizi Dengan Status Gizi Balita Usia 1-5 Tahun Di Desa Kedawung Wilayah Kerja Puskesmas Ngadi - Ira Titisari; Finta Isti Kundarti; Mira Susanti (Akademi Keperawatan Dharma Husada Kediri, 2015)
One of the factors that affect the nutritional status of children is the mother's knowledge. Knowledge is a determinant of attitudes and behavior of the mother. Knowledge required for the application of the provision of food for the nutritional needs so that the nutritional status of children is known. The purpose of this study was analyze the correlation between nutrition knowledge of mothers about nutrition with nutritional status of children aged 1-5 years in Kedawung Village Ngadi health center. The research used cross-sectional method. Total population is 369 children, with proportional sampling techniques and random sampling found 74 respondens and their children as the sample. Data collected by questionnaire and analyzed using the Spearman rank correlation test. The results show respondents have sufficient knowledge about children nutrition is equal to 44.59%. While most respondents children have good nutrition (81.08%). With the Spearman Rank test results obtained ρ = 0,5 with t formula is t value (4,9) > t table (1.993), then Ho is rejected it means there is a correlation between nutrition knowledge of mothers about nutrition with nutritional status of children aged 1-5 years in Kedawung village Ngadi health center. The conclusion is obtained that the better knowledge of the mother's so nutritional status of children will be close to normal. It is therefore suggested to provide information about nutrition. Keywords : Children, Knowledge, Nutritional Status